2004
DOI: 10.1080/1384128042000261800
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality, unemployment, and poverty in Nigeria: a vector autoregressive approach

Abstract: The main features of poverty are low levels of consumption and income, a fact-of-life in most African countries. This paper analyzes the fundamental trends of per capita income, government capital expenditure, the human development index, and the rate of unemployment in the Nigeria. A vector autoregressive model finds that: A reduced unemployment rate improves human development and consequently reduces poverty. As growth in public capital expenditure rises, unemployment falls and the human development index im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 3 publications
0
14
0
3
Order By: Relevance
“…The authors argue that the goals of infrastructure reforms can only be achieved if such reforms are undertaken in the context of appropriate market and regulatory frameworks. Akinbobola and Saibu (2004) investigate the nexus between income inequality, unemployment and poverty in Nigeria using a vector autoregressive (VAR) approach. In this study, quarterly data on real per capita income, government capital expenditure, unemployment rate and the human development index were sourced for the period 1986-2000 and used for the analysis.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…The authors argue that the goals of infrastructure reforms can only be achieved if such reforms are undertaken in the context of appropriate market and regulatory frameworks. Akinbobola and Saibu (2004) investigate the nexus between income inequality, unemployment and poverty in Nigeria using a vector autoregressive (VAR) approach. In this study, quarterly data on real per capita income, government capital expenditure, unemployment rate and the human development index were sourced for the period 1986-2000 and used for the analysis.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…On the one hand, life expectancy is believed to be the single most important factor explaining human development (Ivanova, Arcelus, & Srinivasan, 1999;Ogwang & Abdou, 2003). On the other hand, when examining poverty using the HDI in Nigeria, Akinbobola and Saibu (2004) found that decreasing unemployment and generating income provided the best explanatory power to human development. The HDI is not a comprehensive measure, but rather encompasses average achievement (Fakuda-Parr, 2001).…”
Section: Review Of the Literature Quality Of Lifementioning
confidence: 97%
“…Research done by Defina (2002) revealed that revised poverty headcount rate has a much weaker relationship compared to the official headcount poverty rate. Akinbobola & Saibu (2004) used the human capital index to measure poverty found that when public expenditure increases unemployment decrease and the human capital index improves.…”
Section: Poverty and Unemploymentmentioning
confidence: 99%